Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5005/jp-journals-10005-1833
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Microhardness and Enamel Solubility of Treated Surface Enamel with Resin Infiltrant, Fluoride Varnish, and Casein Phosphopeptide-amorphous Calcium Phosphate: An In Vitro Study

Abstract: A bstract Aim and objective The aim and objective of this study was to do a comparative evaluation of microhardness and enamel solubility (ES) of the treated surface enamel with resin infiltrant, fluoride varnish, and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP). Materials and methods An in vitro study was conducted on freshly extracted 85 sound permanent teeth of which 5 teeth were subjected to check … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Regarding the EDX results, specimens treated with lactoferrin in both DM and PM groups revealed that the decline in Ca weight% was not statistically significant compared with a statistically significant reduction in the P weight%. Ca/P ratio also decreased with no statistical significance, explaining the decline in microhardness, which may be due to the breakdown of hydroxyapatite and loss of mineral content (calcium and phosphorus) [ 32 ]. Demineralization of enamel arises from chemical reactions that cause the major enamel component, hydroxyapatite crystals, to break down.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the EDX results, specimens treated with lactoferrin in both DM and PM groups revealed that the decline in Ca weight% was not statistically significant compared with a statistically significant reduction in the P weight%. Ca/P ratio also decreased with no statistical significance, explaining the decline in microhardness, which may be due to the breakdown of hydroxyapatite and loss of mineral content (calcium and phosphorus) [ 32 ]. Demineralization of enamel arises from chemical reactions that cause the major enamel component, hydroxyapatite crystals, to break down.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that have used the AFM analysis technique [ 42 , 43 , 44 ] have found that the hardness of dental hard tissues decreases after the use of fluoride varnishes. Additionally, fluoride varnish is effective in reducing enamel demineralization [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concern arises when discussing the treatment of superficial interproximal lesions, given the fact that restorative therapy involves removing a considerable amount of sound tissue, thus bringing the tooth into a circle of treatment and retreatment. 1 , 2 Currently, aiming at a minimally invasive and nondestructive odontology, various remineralizing agents could be indicated, such as dental hygiene instruction and fluoride topical application. However, these procedures are limited to the surface of the lesion, not being able to reach the demineralized tissue.…”
Section: Introductionmentioning
confidence: 99%
“…However, these procedures are limited to the surface of the lesion, not being able to reach the demineralized tissue. 1 In addition, requires the cooperation of patients to ensure successful treatment. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation